Airway allergy causes alveolar macrophage death, profound alveolar disorganization and surfactant dysfunction - Feo-Lucas, Lidia; Godio, Cristina; Minguito de la Escalera, María; Alvarez-Ladrón, Natalia; Villarrubia, Laura H.; Vega-Pérez, Adrián; González-Cintado, Leticia; Domínguez-Andrés, Jorge; García-Fojeda, Belén; Montero-Fernández, Carlos; Casals, Cristina; Autilio, Chiara; et al. (Frontiers in Immunology, 2023)
Respiratory disorders caused by allergy have been associated to bronchiolar inflammation leading to life-threatening airway narrowing. However, whether airway allergy causes alveolar dysfunction contributing to the pathology of allergic asthma remains unaddressed. To explore whether airway allergy causes alveolar dysfunction that might contribute to the pathology of allergic asthma, alveolar structural and functional alterations were analyzed during house dust mite (HDM)-induced airway allergy in mice, by flow cytometry, light and electron microscopy, monocyte transfer experiments, assessment of intra-alveolarly-located cells, analysis of alveolar macrophage regeneration in Cx3cr1cre:R26-yfp chimeras, analysis of surfactant-associated proteins, and study of lung surfactant biophysical properties by captive bubble surfactometry. Our results demonstrate that HDM-induced airway allergic reactions caused severe alveolar dysfunction, leading to alveolar macrophage death, pneumocyte hypertrophy and surfactant dysfunction. SP-B/C proteins were reduced in allergic lung surfactant, that displayed a reduced efficiency to form surface-active films, increasing the risk of atelectasis. Original alveolar macrophages were replaced by monocyte-derived alveolar macrophages, that persisted at least two months after the resolution of allergy. Monocyte to alveolar macrophage transition occurred through an intermediate stage of pre-alveolar macrophage and was paralleled with translocation into the alveolar space, Siglec-F upregulation, and downregulation of CX3CR1. These data support that the severe respiratory disorders caused by asthmatic reactions not only result from bronchiolar inflammation, but additionally from alveolar dysfunction compromising an efficient gas exchange.